Measurement of expansion deformation at an expansion joint in a heating network based on information from distributed temperature sensing. (14th March 2019) - Yang, Hanrui; Li, Yongyong; Jiao, Shengxi; Xu, Shibo; Zhang, Jingwei; Luan, Ning
Abstract: As the key parts of a buffer pipeline, expansion joints are usually deformed by expansion of the heat pipe. Accurate measurement of the expansion deformation in real time is one of the necessary conditions for assessing the health of a heating network. In this paper, a detection method for the deformed state is proposed based on information measured by a distributed optical fiber sensing system. In the experiment, a new detector based on an optical fiber cable is constructed for information on the light intensity. Additionally, a numerical model relating the expansion deformation and the amplitude ratio of light intensity is constructed from the experimental data. This indicates that the maximum distance of measurement is more than 420 mm within a relative error of 8.5%. In addition, measurements can be made at temperatures from 26 °C to 85 °C, which is suitable for a heating network.